Delikan, Bentengan, Jamuran, Cublak-Cublak Suweng: Javanese Traditional Games for Character Education Learning - Niswatin Nurul Hidayati (Kariman: Jurnal Pendidikan dan Keislaman, 2021)
This research aimed to describe and analyze how traditional Javanese traditional games have many moral values, so they can be used as a medium for character education. This research used desciptive qualitative approach. The results of the research indicated that in Java there are quite a number of traditional games, for example Delikan, Bentengan, Jamuran, Cublak Cublak Suweng, and so on. Then, because the game is a legacy of the nation's ancestors, in the game there are several moral values that can be used as lessons, such as religiousity, integrity, nationalism, cooperation, and independence. This showed that Javanese traditional games should be well preserved and used as one of ways to implant character education on children and teenagers.